Continuity of ethical views of Haji Bektash Veli and Kazakh religious thinkers - Myrzabekov, M. (Chabaršy. Dintanu serijasy, 2020)
Ahmet Yasawi, Haji Bektash, Abay, Shakarim and other Kazakh scholars had great importance to the inner world of human, also for spiritual purification and moral-ethic development. Because the nature of human is not in glory and honor or in wealth. It is laid in human virtue and purity of heart. Therefore, Abay emphasized the human being in his teachings as the essence and nature of this world. He pointed out the human heart as the main essence. From the point of view of moral and ethical development, the personal human qualities such as spiritual purity, patience, honesty, humility, grace and brotherhood are required in the knowledge of Haji Bektash and Kazakh scholars. Thus, spiritual development requires moral purity, patience, honesty, humility, grace and brotherhood. In this study, we tried to determine the compatibility between views of Haji Bektash Veli and Kazakh religious thinkers. The information used in this study is based on the data obtained by the comparative research method. As a result of these data, we saw that Ahmet Yasawi and Al-Farabi were the basis of the moral understanding of Haji Bektash Veli and Kazakh religious thinkers.